Analisis Pelepasan Beban Sistem Jaringan Bengkulu dengan Penambahan PLTU Teluk Sepang 2x100 MW - Herawati, Afriyastuti (JURNAL AMPLIFIER : JURNAL ILMIAH BIDANG TEKNIK ELEKTRO DAN KOMPUTER, 2023)
Load shedding is one way to overcome the rapid decrease in frequency due to transient disturbances. With load shedding the rate of decrease in system frequency can be slowed down so as to avoid total blackouts in the power system. Currently, the Bengkulu network system has added a new power plant, namely PLTU 2 x 100 MW in Teluk Sepang. This paper analyzes load shedding on the Bengkulu network system after the inclusion of PLTU Teluk Sepang. The proposed method is load shedding taking into account the Rate Of Change Of Frequency (ROCOF) and critical fault clearing time (CCT) after a transient fault occurs and then analyzing the stability of the system transient before and after the load shedding occurs with three phase short circuit disturbance. The analysis found that the proposed method succeeded in returning the dropped frequency to the permitted frequency value and the system showed a stable response after a transient disturbance occurred.